(untitled) (UNWE Yearbook, 2020)
The modern trends in threats to international security, such as the nuclear arms race, terrorist threats through improvised explosive devices with radioactive materials, cyber-threats against hi-tech production and operating security systems, the 2011 earthquake with a 9.0 magnitude on the Richter scale which caused a tsunami, which in turn led to the Fukushima nuclear disaster, have drawn attention to the various dimensions and degrees of the physical vulnerability of nuclear sites and facilities.